32. CLINICAL FEATURES AND RESULTS OF TREATMENT OF PSOAS ABSCESS AT NGUYEN TRI PHUONG HOSPITAL PERIOD 2018-2022 (Vietnam Journal of Community Medicine, 2024)
Background: Psoas muscle abscess is a rare medical condition. The clinical symptoms of a secondary psoas abscess are often atypical. This study aims to understand the pathological features to help diagnose and treat early cases of psoas abscess. Objective: This study describes the clinical and paraclinical characteristics and treatment results of patients with iliopsoas abscesses undergoing intervention. Methods: Retrospective descriptive study of patients who were diagnosed with psoas abscess and treated at Nguyen Tri Phuong Hospital from January 2018 to December 2022. Results: In 29 patients, the mean age was 56,8 ± 14,8; ages 25 to 83 years old. Male accounted for 44,8%, female accounted for 55,2%, male:female ratio was 4:5. History of diabetes 65,5%, spondyloarthritis 31,0%. Fever was the most common reason for hospitalization (58,6%). The majority of psoas abscesses are on the right (62,1%), both sides are 6.9%. The result of pus culture was negative 55,2%, most positive for E. Coli (20,7%); There were 2 cases of PCR positive for TB (accounting for 6,9%). The two most used antibiotic regimens were Ceftriaxon + Metronidazole (31,3%) and Carbapenem + Linezolide (17,2%). After surgical intervention, leukocyte index and abscess volume decreased significantly (p
Keywords: Psoas abscess, drainage surgery.